Toward a multiple perspective in family theory and practice the case of social exchange theory, symbolic interactionism, and conflict theory - Rank, Mark R.; LeCroy, Craig W. (1983)
Examines the complementarity of three often-used theories in family research: social exchange theory, symbolic interactionism, and conflict theory. Provides a case example in which a multiple perspective is applied to a problem of marital discord. Discusses implications for the clinician.
Includes bibliographical references.
Downloaded from http://www.jstor.org/stable/584622
Keywords: Family problems; Family relationships; Family counseling